Optimised force-velocity training during pre-season enhances physical performance in professional rugby league players - Simpson, A.; Waldron, M.; Cushion, E.; Tallent, J. (Journal of Sports Sciences, 2020)
The effectiveness of 8-week force-velocity optimised training was assessed in highly trained professional rugby league athletes. Players (age 24 ± 3 years; body mass 94.9 ± 21.6 kg; height 181.3 ± 6.0 cm) were strength-matched and assigned to a force-velocity optimised group (OP; n = 15) or a general strength-power group (GP; n = 14). Tests included 10-m, 20-m sprints, 3 repetition-maximum squat and squat jumps over five load conditions to ascertain vertical force-velocity relationship. ANCOVA revealed there was a group effect for force-velocity deficit (P < 0.001), with the OP two-fold greater than the GP group (OP pre: 51.13 ± 31.42%, post: 62.26 ± 31.45%, GP pre: 33.00 ± 19.60%, post: 31.14 ± 31.45%, P < 0.001). There were further group effects for 3RM squat (OP pre: 151.17 ± 22.95 kg, post: 162.17 ± 24.16 kg, GP pre: 156.43 ± 25.07 kg, post: 163.39 ± 25.39 kg, P < 0.001), peak power (OP pre: 3195 ± 949 W, post: 3552 ± 1033 W, GP pre: 3468 ± 911 W, post: 3591 ± 936 W, P < 0.001), and SJ (OP pre: 39.79 ± 7.80 cm, post: 42.69 ± 7.83 cm, GP pre: 40.44 ± 6.23 cm, post: 41.14 ± 5.66 cm, P < 0.001). Prescribing F-V deficit training is superior for improving physical performance within highly trained RL players.